ANALISIS PENGARUH BIAYA OPERASIONAL, RISIKO KREDIT, RISK AVERSION, DAN OPPORTUNITY COST TERHADAP NET INTEREST MARGIN PERBANKAN INDONESIA (Studi Pada Bank BUMN, Bank Pembangunan Daerah, dan Bank Umum Swasta Nasional Devisa Periode 2011-2014) - Paramitha, Andreana Dita; Muharam, Harjum (Diponegoro Journal of Management, 2016)
This research aims to analyze the influence of operating cost, credit risk, risk aversion, and opportunity cost to Net Interest Margin (NIM) of banks in Indonesia and to knowing the difference of Net Interest Margin (NIM) in three groups of bank which are state owned banks, regional development banks, and foreign exchange commercial banks. The data used in this research were obtained from the published financial statements during the periods 2011-2014. The sampling technique used was purposive sampling. Sample in this research there were 25 banks, which are 4 state owned banks, 8 regional development banks, and 13 foreign exchange commercial banks. Data is analized using multiple linear regression and linear regression analysis with dummy variables to determine differences Net Interest Margin (NIM) of three groups banks with significance level of 5%. Results of this research show that operating cost and risk aversion have significant positive effect on NIM. Credit risk has significant negative effect on NIM. However opportunity cost has no significant effect on NIM. NIM owned by Foreign Exchange Commercial Banks were 131,6% lower than other groups.